PENEGAKAN HUKUM TINDAK PIDANA TANPA HAK DENGAN SENGAJA TURUT SERTA MENAWARKAN KEPADA KHALAYAK UMUM UNTUK BERMAIN JUDI (Studi Putusan Nomor: 489/Pid.B/2022/PN.Tjk) - Prawira Dinata, Alga (JOURNAL OF INDONESIAN COMPARATIVE OF SYARIAH LAW, 2023)
The aim of the research is to analyze law enforcement efforts made by the police in uncovering the crime of gambling at Tanjung Karang Decision Number: 489/Pid.B/2022/PN.Tjk and to analyze the inhibiting factors faced by the police in handling and uncovering cases of gambling crimes in an effort to enforce the law in Tanjung Karang Decision Number: 489/Pid.B/2022/PN.Tjk. The research method uses normative research. Gambling in Indonesia is not a new problem. The development of gambling in Indonesia has been carried out for a long time. Therefore, every development of gambling in Indonesia needs to be handled seriously by law enforcement officials in order to implement and establish social life that supports better development. Criminal law enforcers in dealing with gambling problems in Indonesia have received many responses from the public regarding the difficulty of law enforcement officials in enforcing criminal law.